The prevalence of varicella zoster virus, herpes simplex virus type 2, and human papillomavirus in breast cancerous tissues and their adjacent ones in Iran - Shaian Tavakolian; Ebrahim Faghihloo (Journal of Research in Medical Sciences, 2023)
Background: Breast cancer is the second type of cancer in the world. Some internal and external risk factors, especially infection diseases, can progress breast cancer. As the relation between varicella zoster virus (VZV), human papillomavirus (HPV), herpes simplex virus type 2 (HSV-2), and breast cancer has not been understood, it was attempting to find the effect of these viruses and breast cancer in this study. Materials and Methods: We collected 40 breast cancer and 50 healthy adjacent tissues from Taleghani and Imam Hossein Hospital, Tehran, Iran, in 3 years starting in 2017. After extracting DNA from breast tissues, multiplex polymerase chain reaction (PCR), nested PCR, and PCR were done to analyze the prevalence of HSV-2, VZV, and HPV. Results: Our results showed that HPV may be one of the important causes of breast cancer. Nested PCR illustrated nine breast cancerous tissues (mean age: 43) and three healthy adjacent ones (mean age: 41) were infected by HPV. Phylogenetic analysis illustrated that all of the infected HPV cancerous and healthy tissues were HPV 18 (except two healthy samples infected with HPV 6). Nevertheless, there were not any infected tissues by HSV-2 and VZV. Conclusion: It seems that HPV virus type 18 can have high prevalence in breast cancerous tissues in comparison with healthy adjacent ones, and it is likely to have an effect on breast cancer progression. However, the opposite trend is true for HSV-2 and VZV as we did not find any differences between different kinds of breast tissues.